2016
DOI: 10.1002/mus.25223
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve high‐resolution ultrasound in diabetes

Abstract: Peripheral nerves are enlarged diffusely in diabetic patients, including sites not susceptible to bony compression. The number of enlarged CSA values can help predict the presence of DSP. Muscle Nerve, 2016 Muscle Nerve 55: 171-178, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 26 publications
8
67
1
1
Order By: Relevance
“…As the sites of asymmetrical CSA increase involved mostly the median nerve at the carpal tunnel and the fibular nerve in the fibula head, we could assume that RLS patients present with a relative CSA increase in compression sites. This assumption is surely in agreement with previous studies on axonal diabetic neuropathy, which also show increased CSA in compression sites showing a vulnerability of degenerated nerves to mechanical compression …”
Section: Discussionsupporting
confidence: 93%
“…As the sites of asymmetrical CSA increase involved mostly the median nerve at the carpal tunnel and the fibular nerve in the fibula head, we could assume that RLS patients present with a relative CSA increase in compression sites. This assumption is surely in agreement with previous studies on axonal diabetic neuropathy, which also show increased CSA in compression sites showing a vulnerability of degenerated nerves to mechanical compression …”
Section: Discussionsupporting
confidence: 93%
“…Riazi et al found that the posterior tibial nerve was smaller and thinner in patients with type 1 DM and DPN. Breiner et al found thicker peripheral nerves in patients with type 1 DM than healthy volunteers in an adult population, but the mean cross‐sectional area of the nerves was thinner than in patients with type 2 DM. Metabolic factors in patients with DM can cause demyelination of the peripheral nerves and loss of axons.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, we found significant differences in the cross‐sectional area and thickness of the posterior tibial nerve on both axes, but the median nerve did not show any differences. Several studies have shown that in diabetic patients, the cross‐sectional areas of nerves have various correlations with the type and severity of the disease . Dikici et al found a difference between the cross‐sectional area of the anterior tibial nerve in patients with type 2 DM and symptoms of DPN and a control group, whereas there was no difference for asymptomatic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Most acquired or idiopathic axonal neuropathies show either no nerve enlargement or only mild nerve enlargement on average, with considerable overlap in nerve size between patients and control subjects. In diabetes mellitus, for instance, nerves are on average slightly enlarged compared with control subjects, with more prominently enlarged nerves in those with more poorly controlled diabetes and in those with diabetic peripheral neuropathy . In sarcoidosis, 1 study of 13 patients showed only slightly larger tibial, peroneal, and sural nerves compared with control subjects .…”
Section: Nerve Sonography In Other Polyneuropathiesmentioning
confidence: 95%